2010
DOI: 10.1042/bj20091011
|View full text |Cite
|
Sign up to set email alerts
|

Filamin associates with stress signalling kinases MKK7 and MKK4 and regulates JNK activation

Abstract: SAPK/JNK (stress-activated protein kinase/c-Jun N-terminal kinase) belongs to the MAPK (mitogen-activated protein kinase) family and is important in many biological contexts. JNK activation is regulated by phosphorylation of specific tyrosine and threonine residues sequentially catalysed by MKK4 and MKK7, which are both dual-specificity MAPKKs (MAPK kinases). Previously, we reported that tyrosine-phosphorylation of JNK by MKK4 precedes threonine-phosphorylation by MKK7, and that both are required for synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…Sun et al (23) reported that MEKK4 could stimulate JNK and p38 activation in the human prostate adenocarcinoma cell line after tumor necrosis factor-related apoptosis-inducing ligand treatment, which might contribute to cell apoptosis. Nakagawa et al (19) reported MKK4 and MKK7 sequentially phosphorylated tyrosine and threonine residues of JNK, respectively, and phosphorylation of both residues would lead to synergistic JNK activation in stress-stimulated embryonic stem cells, which might play an important role in stress signaling. However, to our knowledge, no data about the role of MEKK4, MKK4, or MKK7 in TGF-␤1 expression were reported previously.…”
Section: Discussionmentioning
confidence: 98%
“…Sun et al (23) reported that MEKK4 could stimulate JNK and p38 activation in the human prostate adenocarcinoma cell line after tumor necrosis factor-related apoptosis-inducing ligand treatment, which might contribute to cell apoptosis. Nakagawa et al (19) reported MKK4 and MKK7 sequentially phosphorylated tyrosine and threonine residues of JNK, respectively, and phosphorylation of both residues would lead to synergistic JNK activation in stress-stimulated embryonic stem cells, which might play an important role in stress signaling. However, to our knowledge, no data about the role of MEKK4, MKK4, or MKK7 in TGF-␤1 expression were reported previously.…”
Section: Discussionmentioning
confidence: 98%
“…Although only one substrate, Rab1, was studied in depth in this study, a number of these substrates fit with known characteristics of TAK1 signaling. Filamin A functions as a scaffold for MKK4 and JNK association and activation of JNK (41,42). MKK4 is a direct substrate of TAK1, thus it is possible TAK1 also associates with Filamin A to stimulate MKK4/JNK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phosphorylation of myosin light chain kinase (MLCK) and filamin by MAPK has been reported, as has an effect of phosphorylation on their activity and subsequent cytoskeletal reorganization (He et al, 2003;Nakagawa et al, 2010;Kim and McCulloch, 2011). As discussed above, filamin has been identified in a complex with ␤-arrestins and ERK1/2.…”
Section: ␤-Arrestin-scaffolded Mapks and Cytoskeletal Reorganizationmentioning
confidence: 99%